Factors associated with unsatisfactory cosmetic results in oncoplastic surgery - de Oliveira-Junior, Idam; da Costa Vieira, René Aloísio; Biller, Gabriele; Sarri, Almir José; da Silva, Fabíola Cristina Brandini; Nahás, Eliana Aguiar Petri (Frontiers in Oncology, 2023)
Introduction: Oncoplastic surgery (OS) has expanded the indications for breast-conserving surgery associated with an adequate aesthetic result. However, few studies have described the factors associated with unsatisfactory cosmetic outcomes from this surgical modality. Materials and methods: This is a cross-sectional prospective study that included patients undergoing breast-conserving surgery (BCS) with or without OS. The patients self-evaluated the cosmetic results of the breasts posttreatment and had them photographed. The photos were analyzed by BCCT.core. Individual and treatment factors (local and systemic) for all patients were evaluated. These factors were dichotomized according to the use of OS and to the cosmetic result (satisfactory and unsatisfactory). Categorical variables were tested for association with surgical outcome using the chi-square test while numerical variables using the Mann‒Whitney U test. Variables with p <0,2 were selected for multivariate analysis. Results: Of the 300 patients evaluated, 72 (24,0%) underwent OS. According to the patient self-evaluations, an unsatisfactory cosmetic result from OS was significantly associated with younger age at diagnosis, higher body mass index (BMI) at the time of evaluation, larger tumor size and greater weight of the surgical specimen. According to the BCCT.core, only the laterality of the tumor (left) was significantly associated with an unsatisfactory cosmetic result. In logistic regression, considering OS as a control variable, the risk of an unsatisfactory outcome according to patient self-evaluation was related to the tumor ≥ T2 odds ratio (OR) 1,85 (1,027-3,34) and age at diagnosis < 40 [OR 5,0 (1,84-13,95)]. However, according to the software, the variables were associated with an increased risk of an unsatisfactory outcome were the time interval between surgery and evaluation [OR 1,27 (1,16-1,39)], the presence of lymphedema [OR 2,97 (1,36-6,46)], surgical wound infection [OR 3,6 (1,22-11,16)], tumor location on the left side [OR 3,06 (1,69-5,53)], overweight [OR 2,93 (1,48-5,8)] and obesity [OR 2,52 (1,2-5,31)]. Conclusion: There is no standard methodology for breast cosmesis evaluation, which influences the factors associated with unsatisfactory results. Younger patients and those with increased BMI, left breast cancer and extensive resections tend to present with unsatisfactory cosmetic results when OS is performed.